A fast and zero-biased photodetector based on GaTe–InSe vertical 2D p–n heterojunction. (1st February 2018) - Feng, W; Jin, Z; Yuan, J; Zhang, J; Jia, S; Dong, L; Yoon, J; Zhou, L; Vajtai, R; Tour, J M; Ajayan, P M; Hu, P; et al.
Abstract: p–n junctions serve as the building blocks for fundamental semiconductor devices, such as solar cells, light-emitting diodes (LEDs) and photodetectors. With recent studies unveiling the excellent optoelectronic properties of two-dimensional (2D) semiconductors, they are considered to be superb candidates for high performance p–n junctions. Here, we fabricate a vertical GaTe–InSe van der Waals (vdWs) p–n heterojunction by a PDMS-assisted transfer technique without etching. The fabricated p–n heterojunction shows gate-tunable current-rectifying behavior with a rectification factor reaching 1000. In addition, it features fast photodetection under zero bias as well as a high power conversion efficiency (PCE). Under 405 nm laser excitation, the zero-biased photodetector shows a high responsivity of 13.8 mA W −1 as well as a high external quantum efficiency (EQE) of 4.2%. Long-term stability is also observed and a response time of 20 µ s is achieved due to stable and fast carrier transit through the built-in electric field in the depletion region. Fast and efficient charge separation in the vertical 2D p–n junction paves the way for developing 2D photodetectors with zero dark current, high speed and low power consumption.